Fourth ACM and IEEE International Conference on Formal Methods and Models for Co-Design, 2006. MEMOCODE '06. Proceedings.
DOI: 10.1109/memcod.2006.1695901
|View full text |Cite
|
Sign up to set email alerts
|

802.11a transmitter: a case study in microarchitectural exploration

Abstract: Hand-held devices have rigid constraints regarding power dissipation and energy consumption. Whether a new functionality can be supported often depends upon its power requirements. Concerns about the area (or cost) are generally addressed after a design can meet the performance and power requirements. Different micro-architectures have very different area, timing and power characteristics, and these need RTL-level models to be evaluated. In this paper we discuss the microarchitectural exploration of an 802.11a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…To name just a few, [6] is an example of a design with streaming reuse, and cores with streaming and iterative reuse are developed in [2,4,8].…”
Section: Related Workmentioning
confidence: 99%
“…To name just a few, [6] is an example of a design with streaming reuse, and cores with streaming and iterative reuse are developed in [2,4,8].…”
Section: Related Workmentioning
confidence: 99%
“…Most importantly, Bluespec compiler offers the ability to synthesize high-quality circuits in a "push-button" manner. Several studies have shown that it is possible to create designs in Bluespec very quickly and once a design is working, to modify its parts to gain much deeper insights into the cost and effectiveness of sub-blocks [2,4,14].…”
Section: Introductionmentioning
confidence: 99%
“…We use a folded pipeline design using the same Bluespec pipelining Table 2. Area and Power Dissipation of WUSB Transmitter framework [5]. Thus it is easy to quickly change the area/performance tradeoff.…”
Section: Technical Resultsmentioning
confidence: 99%
“…The project started out focusing on studying the cost-area tradeoffs possible in the RTL design of a 802.11a transmitter [5]. As the project progressed it became clear that many of the key blocks in both the transmitter and reciever, the receiver size, it then became clear that many of the key blocks, while complex, were reusable across multiple OFDM-based protocols.…”
Section: Ofdm Frameworkmentioning
confidence: 99%